2006
DOI: 10.1002/jbt.20112
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite binding to synthetic peptides: The effect of increasing length between two cysteines

Abstract: We utilized radioactive 73As-labeled arsenite and vacuum filtration methodology to determine the binding affinity of arsenite to eight synthetic peptides ranging from 13 to 24 amino acids long and containing one or two cysteines separated by 0-17 intervening amino acids. Six of the eight peptides were highly similar in amino acid sequence and were based on cysteine containing regions of the hormone-binding site of the human estrogen receptor-alpha (e.g., the sequence of peptide 28 is LEGAWCGKGVEGTEHLYSMKCKNV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 24 publications
2
39
1
Order By: Relevance
“…Although it has been suggested that vicinal cysteine residues are required for high affinity arsenite binding (33), our current findings indicate that vicinal cysteines are not necessarily sufficient for arsenite binding to peptides (Figs. 4 and 5) or disruption of zinc binding in cells (Figs.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Although it has been suggested that vicinal cysteine residues are required for high affinity arsenite binding (33), our current findings indicate that vicinal cysteines are not necessarily sufficient for arsenite binding to peptides (Figs. 4 and 5) or disruption of zinc binding in cells (Figs.…”
Section: Discussioncontrasting
confidence: 88%
“…Our studies demonstrate arsenite binding selectivity in both peptide and protein with a link between interaction and functional consequences for protein activity. Although arsenite may be capable of binding to a C2H2 zinc finger (32,33,43), the final product may not persist for a sufficient length of time to be detected by MALDI-TOF-MS. This difference in chemical kinetics could have major impact in cells, where a more stable interaction of arsenite with a C3 or C4 zinc finger protein may be necessary to sustain biological impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this and prior studies [13,27] have given us a more comprehensive view (both in respect to kinetics of dissociation and association of complexes and the K d and B max values) of the intermolecular and intramolecular way in which arsenite binds to cysteine-containing peptides and thus, proteins.…”
Section: Discussionmentioning
confidence: 94%
“…For triand bi-dentate arsenicals (i.e., arsenite and MMA(III)), binding can crosslink two or three different peptides or proteins forming new homo or hetero dimer or trimer forms of the original peptides and proteins. Arsenite is capable of binding with high affinity to two cysteine moieties that are a surprisingly large distance (14 intervening amino acids) apart [27].…”
Section: Arsenite Binding To Monothiol Dithiol and Trithiol Peptidementioning
confidence: 99%